EFEKTIVITAS PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP RETENSI SISWA PADA MATA PELAJARAN IPS DI KELAS V SEKOLAH DASAR - Adrian, Yudha (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
The objective this study is to find out the effect of cooperative learning tipe STAD toward students’ retention on Social Studies at fifth grade in elementary school. This study is experimental study using a quasy experiment. Design of study is nonequivalent control group design. Data analysis used the independent t-test is helped IBM SPSS 21. The result of study showed that p value 0.05 or statistic null is accepted. In short, there is no diffrerences cooperative learning tipe STAD toward students’ retention of grade fifth of elementary school on Social Studies. Suggestion for next researcher is to examine the effect of cooperative learning tipe STAD to other variable, expecially retention variable.Keywords: cooperative learning, STAD, and retention